Cerebral vasoreactivity is impaired in treated, virally suppressed HIV-infected individuals. (2nd January 2016) - Chow, Felicia C.; Boscardin, W. John; Mills, Claire; Ko, Nerissa; Carroll, Courtney; Price, Richard W.; Deeks, Steven; Sorond, Farzaneh A.; Hsue, Priscilla Y.
Abstract : Objective: To compare cerebral vasoreactivity, a measure of cerebrovascular endothelial function, between treated, virally suppressed HIV-infected individuals and HIV-uninfected controls and to evaluate the effect of HIV-specific factors on cerebral vasoreactivity. Methods: Cross-sectional study of 65 antiretroviral therapy-treated, virally suppressed HIV-infected individuals and 28 HIV-uninfected controls. Participants underwent noninvasive assessment of cerebral vasoreactivity using transcranial Doppler ultrasound and inhaled carbon dioxide (CO2 ). We used mixed effects multivariable linear regression to determine the association of HIV infection and HIV-specific factors with cerebral vasoreactivity. Results: Mean age was 57.2 years for HIV-infected participants and 53.5 years for HIV-uninfected controls. Most participants (95%) were men. Twenty-six per cent of HIV-infected participants were nonwhite compared to 32% of controls. Among HIV-infected participants, mean CD4 + cell count was 596 cells/μl, and mean duration of viral suppression was 7.8 years. Cerebral vasoreactivity in response to hypercapnia (cerebral VRhyper ) was lower in HIV-infected individuals compared to uninfected controls (3.23 versus 3.81%, P = 0.010). After adjusting for demographic and vascular risk factors, HIV infection was independently associated with lower cerebral vasoreactivity (–0.86%, 95% CI –1.30 to –0.42%, P < 0.001). We did not find a statistically significant effect of recent or nadir CD4 + cell count on cerebral vasoreactivity. There was a trend toward higher cerebral vasoreactivity for each additional year of viral suppression. Conclusion: Treated, virally suppressed HIV infection negatively impacted cerebral vasoreactivity even after adjustment for traditional vascular risk factors. These data highlight the potential contribution of cerebrovascular endothelial dysfunction to the elevated risk of stroke observed in HIV-infected individuals.